2014
DOI: 10.1097/cji.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of Ipilimumab

Abstract: In this named-patient program including heavily pretreated patients, the efficacy and tolerability of ipilimumab 3 mg/kg corresponds with findings from the confirmatory clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
7
19
0
Order By: Relevance
“…In our study, four doses of ipilimumab, the absence of brain metastases, and an ALC ≥1000/µl at week 4 were identified as factors independently associated with a better OS in the 83 patients with cutaneous melanoma. These findings enforce the current level of evidence gained by several studies that the completion of the four-dose-induction phase [ 14 , 26 ], the absence of brain metastases [ 14 16 ], and high ALC counts and/or changes in ALC pharmacodynamics [ 16 18 , 26 29 ] are predictive for a significant prolongation of survival of ipilimumab-treated patients. Investigations continue to further clarify the role of ALC as an on-treatment pharmacodynamic marker of ipilimumab activity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, four doses of ipilimumab, the absence of brain metastases, and an ALC ≥1000/µl at week 4 were identified as factors independently associated with a better OS in the 83 patients with cutaneous melanoma. These findings enforce the current level of evidence gained by several studies that the completion of the four-dose-induction phase [ 14 , 26 ], the absence of brain metastases [ 14 16 ], and high ALC counts and/or changes in ALC pharmacodynamics [ 16 18 , 26 29 ] are predictive for a significant prolongation of survival of ipilimumab-treated patients. Investigations continue to further clarify the role of ALC as an on-treatment pharmacodynamic marker of ipilimumab activity.…”
Section: Discussionsupporting
confidence: 86%
“…The reported OS rate at 12 months of 38 % for patients with cutaneous melanoma is fitting with data from several other studies (range 33–38 %) (Additional file 4 : Table S4) enrolling daily clinical routine patients with a high portion of this melanoma subgroup [ 14 17 ]; a report on an EAP run in the Netherlands and the UK with cutaneous melanoma patients only also resulted into an 1-year OS rate of 38 % [ 18 ]. In a pivotal, randomized phase II dose-ranging study, in which patients with ocular and mucosal melanoma were excluded as well as patients with brain metastases, the OS rate at 12 months for the ipilimumab 3 mg/kg arm of a similar size was 39 % [ 19 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Across disease sites, patients who experience IRAEs while on therapy with anti-PD-1 and anti-PD-L1 antibodies have been documented to experience improved outcomes as measured by overall response rate (ORR), progression-free survival (PFS) and overall survival (OS) [1320]. In patients treated with anti-CTLA-4 antibodies, this association has been less uniform [2125]. Key questions regarding the complete nature of the relationship between IRAEs and ICI efficacy remain unsettled.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate analysis showed that absence of toxicity was a prognostic factor for poor overall survival (OS) and progression-free survival. In an analysis of 198 patients in Germany treated with ipilimumab, the occurrence of immune-related adverse events correlated significantly with response to treatment and prolonged OS [13].…”
Section: Discussionmentioning
confidence: 99%